Digital for Public Administration - Maneerat, Anan; Tharakorn, Akin (Journal of Human and Society, Sisaket Rajabhat University, 2022)
This article “Digital for Public Administration” aims to study and analyze the application of digital technology in the administration and operation of government organizations that comply with the rapidly changing and dynamic world situation. The essences consist of concepts and theories about Digital Organization, Digital Government development, Digital Government features, technology used in Digital Government, the Digital Government’s approach to Data Centric and e-Participation among the world’s leading countries, and other case studies. The analytical method is Analytic Induction by interpreting the conclusions of information, visual phenomena or tangible objects from various secondary data such as documents, textbooks, laws, academic articles, and related research. Moreover, this article aims to enhance knowledge and understanding of the principles and fundamentals of Digital Government and to create guidelines for applying digital technology to work in both public and private organizations that are up to date and consistent with the context of a dynamic society for executives, personnel, academics, teachers, students, the public, and interested people. It is also guidelines for creating good government executives and people in the modern era, which is an important force in driving and developing the country sustainably.